EVALUASI PEMBELAJARAN MENGGUNAKAN LMS SCHOOLOGY PADA MATAKULIAH COMPUTER APPLICATION - Wakhidah, Rokhimatul; Maftuh, Moh Farid (EDUTECH, 2018)
Abstract. This research aimed to determine the evaluation of learning outcomes that have used LMS Schoology in the learning process compared to the previous semester on Computer Ap-plication Course that has not been using LMS. The evaluation is seen from the ability of lecturers in the use of LMS Schoology, to know the ability of students in the use of LMS Schoology, and to know the communication activity of lecturers and students in LMS Schoology. LMS Schoology is used as part of the blended learning model, which is collaborate class learning with online learn-ing. The research used descriptive qualitative method. Data collection tool was questionnaire is given to students who have used LMS Schoology. The study was conducted on English Language Students of 2nd Semester year academic 2016/2017. Data analysis technique used in analyzing questionnaire score is by calculating the percentage of the answer. As a basis for decision making on the assessment of the use of LMS Schoology, the qualification criteria adapted from Arikunto were used. The results showed that lecturers have been able to use the basic features of LMS. Stu-dents are able to use the features of downloading material and uploading tasks. Lecturers who also act as observer and researcher still have not maximized some of the existing features provided by the LMS. The lecturers and students were less active as lecturer still use direct communication rather than communication through news update on LMS.Â Abstrak. Penelitian ini bertujuan untuk mengetahui evaluasi hasil pembelajaran yang telah menerapkan LMS Schoology di dalam proses pembelajaran dibandingkan dengan matakuliah Computer Application semester sebelumnya yang belum menggunakan LMS. Evaluasi yang di-maksud dilihat dari kemampuan dosen dalam penggunaan LMS Schoology, untuk mengetahui kemampuan mahasiswa dalam penggunaan LMS Schoology, dan untuk mengetahui keaktifan komunikasi dosen dan mahasiswa di dalam LMS Schoology. LMS Schoology digunakan sebagai bagian dari model pembelajaran blended learning, yaitu pembelajaran di kelas yang memadukan dengan pembelajaran online. Penelitian menggunakan metode kualitatif deskriptif. Alat pengum-pul data berupa angket yang diberikan kepada mahasiswa yang telah menggunakan LMS Schoolo-gy. Penelitian dilakukan terhadap Mahasiswa Bahasa Inggris Semester 2 TA 2016/2017. Teknik analisis data yang digunakan dalam menganalisis skor angket yaitu dengan menghitung persentase jawaban. Sebagai dasar pengambilan keputusan tentang penilaian penggunaan LMS Schoology, digunakan kriteria kualifikasi yang diadaptasi dari Arikunto. Hasil penelitian menunjukkan bahwa dosen sudah mampu menggunakan fitur dasar LMS. Mahasiswa mampu menggunakan fitur mengunduh materi dan mengunggah tugas. Keaktifan dosen dan mahasiswa masih kurang karena dosen masih menggunakan komunikasi secara langsung daripada melalui pembaruan kabar melalui LMS.